2021
DOI: 10.1186/s12885-021-08521-0
|View full text |Cite
|
Sign up to set email alerts
|

The platelet to lymphocyte ratio is a potential inflammatory marker predicting the effects of adjuvant chemotherapy in patients with stage II colorectal cancer

Abstract: Background The effects of adjuvant chemotherapy in patients with stage II colorectal cancer (CRC) has been in controversy for a long time. Our study aimed to find an effective inflammatory marker to predict the effects of chemotherapy. Methods Seven hundred eight stage II CRC patients in our institution were included. The subpopulation treatment effect pattern plot (STEPP) analysis was used to determine the optimal inflammatory marker and cut-off v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 60 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…analyzed 708 stage II CRC patients. They found that chemotherapy patients with high PLR had significantly longer overall survival and cancer-specific survival than non-chemotherapy patients ( 30 ). However, Davari et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…analyzed 708 stage II CRC patients. They found that chemotherapy patients with high PLR had significantly longer overall survival and cancer-specific survival than non-chemotherapy patients ( 30 ). However, Davari et al.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, NVI was associated with the poor prognosis of stage III patients. overall survival and cancer-specific survival than non-chemotherapy patients (30). However, Davari et al also analyzed 184 locally recurrent rectal cancer patients and found that NLR >3.9 and PLR >275 were related to a lower 5-yr overall survival (31).…”
Section: The Platelet-lymphocyte-ratio (Plr) Is Closely Related To Thementioning
confidence: 99%
“…PLR can be used to assess the dynamic balance between anti-tumor immunity in vivo. When PLR is high, there is an immune imbalance between anti-tumor and tumor-promoting ( 23 ). Catal’s team research shows that PLT supports the formation of blood vessels in tumor tissues, the growth and diffusion of cancer cells and subsequent secondary lesions; PLR is related to the size and degree of tumor invasion ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…It's reported that colorectal cancer patients with a high level of PLR respond better to chemotherapy [22].…”
Section: Discussionmentioning
confidence: 99%